Enterprise creation at a local scale - determining factors in the case of municipalities in Castilla y León - Pedro Moyano; Beatriz Fari\~na; Guillermo Aleixandre; Olga Ogando (European Regional Science Association (ERSA), 2005)
The behaviour of enterprises in terms of their spatial distribution is increasingly drawing the attention of regional science, due to the fact that regional economic development is the result of the complex interaction of various factors, key amongst which is entrepreneurial demography. Yet, as the Organisation for Economic Co-operation and Development has recognised, few empirical studies have addressed the link between new enterprises and economic change at a local scale, despite entrepreneurs constituting one means of creating employment and increasing local community wealth. Within this context, this paper pinpoints those factors that determine the birth of new enterprises at a local scale, focusing on towns in the Spanish Autonomous Region of Castilla y León. The information used was gathered from the approximately 15 000 companies set up between 2001 and 2003 in the 270 towns with over 1 000 inhabitants in the region, and whose creation as a company was published in the Official Journal of the Trade Register Office. The approach used is based on the link between entrepreneurial capacity and regional economic growth, prior to an analysis of regional differences in the setting up of companies within the Spanish economy. Subsequently, a detailed analysis is made of the factors that influence the creation of new enterprises in towns in Castilla y León, through the use of a regression model which, amongst other conclusions, attributes the emergence of enterprises to a large extent to the presence of agglomeration economies and urban growth.
Keywords: 330